Fatwa Ali Jum’ah tentang Nikah ’Urfi: Analisis Maqasid al-Syari’ah dalam Hukum Keluarga Islam Kontemporer - Hanifa, Reza (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
The practice of marriage without official registration (nikah 'urfi) has shown a significant increase in various Muslim countries, including Egypt and Indonesia. This phenomenon has generated tension between religious validity and state legal recognition, giving rise to social and legal problems as well as challenges in the protection of civil rights, particularly for women and children. This article aims to analyze the fatwa of Ali Jum’ah on nikah 'urfi using the framework of maqasid al-sharia. This study employs a normative–philosophical approach through content analysis, combined with a comparative examination of Ali Jum’ah’s fatwa and classical as well as contemporary fiqh literature. The findings indicate that although Ali Jum’ah acknowledges the formal validity of nikah 'urfi from a fiqh perspective, he considers the practice to be contrary to the maqa?id al-sharia because it threatens the protection of lineage (hifzh al-nasl), human dignity (hifzh al-'ird), and civil rights (hifzh al-huquq). Consequently, marriage registration is viewed as a shari' obligation aimed at safeguarding family welfare and ensuring social stability. This article concludes that Ali Jum’ah’s maqa?id-based approach represents a model of contemporary ijtihad capable of bridging classical fiqh and the legal demands of the modern nation-state.